Adding Fillers to Change the Mechanical Behaviour of the Glass Composite Materials - Cerbu, Camelia; Teodorescu, Horatiu; Scutaru, Luminita (My University, 2011)
Abstract— The paper proposes a way of using of the recycled rubber as filler to manufacture a hybrid composite material based on epoxy resin reinforced with glass woven fabrics. Two composite materials are analysed: an epoxy composite material reinforced only with glass fibres; a hybrid composite reinforced both with glass fibres and recycled rubber. The same kind of glass woven fabric is used in both cases. One comparatively presents the mechanical characteristics of these composite materials, measured in: flexural test by using the method of the three points and impact testing. Additionally, the modulus of elasticity E and maximum normal stress σ are determinate in tensile test in case of the new hybrid composite. Moreover, it was analysed the free vibrations of a rectangular plate made of the hybrid composite. Finally, the natural frequencies and the damping factor were obtained. One observed that additionally reinforcing with rubber particles lead to the increasing of the impact strength.
Keywords: glass; rubber; flexural test; tensile test; recycling